2012
DOI: 10.1097/mol.0b013e3283508c4f
|View full text |Cite
|
Sign up to set email alerts
|

Bone marrow transplantation as an established approach for understanding the role of macrophages in atherosclerosis and the metabolic syndrome

Abstract: BMT is an efficient and versatile tool for assessing the roles of specific genes that are restricted to hematopoietic cells, and especially the monocytes and macrophages in metabolic syndrome and its related pathologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
10
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…After 8 weeks of HFD feeding, AIBP ΔBMK /LDLR −/− showed severe atherosclerotic lesions, inflammatory cell infiltration and polarization of macrophages to the proinflammatory phenotype compared with AIBP WT /LDLR −/− mice, indicating that intracellular AIBP may exert anantiatherosclerotic effect. A previous study has reported that BMT normally affects the development of aortic atherosclerosis in mice [ 40 ], but the application of this modality in atherosclerosis is mixed and warrants further investigation [ 41 , 42 ]. In the present study, we used mouse littermates with different genotypes and simultaneously performed BMT transplantation controls.…”
Section: Discussionmentioning
confidence: 99%
“…After 8 weeks of HFD feeding, AIBP ΔBMK /LDLR −/− showed severe atherosclerotic lesions, inflammatory cell infiltration and polarization of macrophages to the proinflammatory phenotype compared with AIBP WT /LDLR −/− mice, indicating that intracellular AIBP may exert anantiatherosclerotic effect. A previous study has reported that BMT normally affects the development of aortic atherosclerosis in mice [ 40 ], but the application of this modality in atherosclerosis is mixed and warrants further investigation [ 41 , 42 ]. In the present study, we used mouse littermates with different genotypes and simultaneously performed BMT transplantation controls.…”
Section: Discussionmentioning
confidence: 99%
“…In this study we examined the effects of macrophage deficiency of α7nAChR on the characteristics of early and advanced stage atherosclerotic lesions in low density lipoprotein receptor knockout (LDLRKO) mice. To that end, we utilized a bone marrow transplantation approach, a strategy used successfully by our laboratory and others to study the contribution of a particular gene expressed by macrophages to atherogenesis [ 15 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…Importantly, the present studies as well as those by Johansson et al [ 13 ] and Kooijman et al [ 14 ] are based on a bone marrow transplantation approach that uses donors with global deficiency of α7nAChR. Whereas this strategy has been successfully used by us [ 15 ] and others [ 19 , 31 , 32 ] to evaluate the contribution of a particular gene expressed by macrophages to atherogenesis, it is difficult to conclude whether the reduction in advanced lesion burden and macrophage content in mice with bone marrow deficiency of α7nAChR is the result of the impact of α7nAChR deficiency on macrophage functions or whether cells other than macrophages also contribute to the observed phenotype. Future studies in mice with macrophage specific deletion of α7nAChR will provide more definitive answers to these questions.…”
Section: Discussionmentioning
confidence: 96%
“…This approach is standard in the atherosclerosis literature and is usually interpreted as indicating myeloid specificity and even implied specificity for macrophages. [30][31][32][33][34] Recipient Ldlr -/mice were preconditioned with lethal c-irradiation, then rescued by adoptive transfer of bone marrow from mice deficient in AMPK (Prkab1 -/-) or littermate matched (Prkab1 þ/þ ) controls. BMT was performed at age 12 weeks, and metformin treatment from age 14 weeks to age 25 weeks, allowing a prolonged period on metformin after BMT, when there was a cull for analysis as for the first cohort (Figure 2A).…”
Section: Atherosclerosis-prevention By Metformin Requires Haematopoietic Ampkmentioning
confidence: 99%